2021
DOI: 10.1155/2021/6626842
|View full text |Cite
|
Sign up to set email alerts
|

Applied Mechatronics: Designing a Sliding Mode Controller for Active Suspension System

Abstract: The suspension system is referred to as the set of springs, shock absorbers, and linkages that connect the car to the wheel system. The main purpose of the suspension system is to provide comfort for the passengers, which is created by reducing the effects of road bumpiness. It is worth noting that reducing the effects of such vibrations also diminishes the noise and undesirable sound as well as the effects of fatigue on mechanical parts of the vehicle. Due to the importance of the abovementioned issues, the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Although a car suspension system has a stochastic nature due to road bumps, except in some cases like Moghadam and Kebriaei (2019), Azizi and Mobki (2021), and Wang (2021), our survey interestingly showed that robust controller, rather than a robust stochastic controller, has been designed to activate a car suspension system. In other words, in the process of controller design, the disturbance due to surface roughness has been considered as an uncertainty, rather than a stochastic process, with known or unknown bound which might cause a conservative controller.…”
Section: Introductionmentioning
confidence: 92%
“…Although a car suspension system has a stochastic nature due to road bumps, except in some cases like Moghadam and Kebriaei (2019), Azizi and Mobki (2021), and Wang (2021), our survey interestingly showed that robust controller, rather than a robust stochastic controller, has been designed to activate a car suspension system. In other words, in the process of controller design, the disturbance due to surface roughness has been considered as an uncertainty, rather than a stochastic process, with known or unknown bound which might cause a conservative controller.…”
Section: Introductionmentioning
confidence: 92%
“…A drawback still exists when using the SMC algorithm, which is the phenomenon of "chattering." Tis phenomenon will cause the signal to vibrate continuously [53]. Terefore, it can afect the quality of the system.…”
Section: Control Algorithmsmentioning
confidence: 99%
“…According to Azizi and Mobki, the objects will slide over the surface. The object then advances toward the location of equilibrium 27 . According to Nguyen, a sliding surface is a complicated function dependent on the controller's error signal 28 .…”
Section: Introductionmentioning
confidence: 99%